Cytotoxicity of intermaxillary orthodontic elastics of different colors: an in vitro study - Rogério Lacerda dos Santos; Matheus Melo Pithon; Gabriella da Silva Mendes; Maria Teresa Villela Romanos; Antônio Carlos de Oliveira Ruellas (University of São Paulo, 2009)
OBJECTIVES: Natural latex does not fall into the category of materials known to be entirely inoffensive. The purpose of this in vitro study was to test the hypothesis that there is no difference in the cytotoxicity between elastics of different colors and those from different manufacturers. MATERIAL AND METHODS: Different latex intraoral elastics of different colors (5/16 = 7.9 mm, mean load) were compared. The sample was divided into 7 groups of 24 elastics each: Group T (TP Orthodontics, natural latex elastics, control); Groups U1, U2, U3, U4, U5 and U6 (Uniden, natural latex elastics and colored elastics, namely, green, pink, yellow, red and purple, respectively). Cytotoxicity assays were performed by using cell culture medium containing epithelioid-type cells (Hep-2 line) derived from human laryngeal carcinoma. The cytotoxicity was evaluated by using the "dye-uptake" test, which was employed at two different moments (0 and 24 h). Data were compared by analysis of variance (ANOVA) and Tukey's test (p<0.05). RESULTS: There was statistically significant difference (p<0.05) between Group T and all other groups (U1, U2, U3, U4, U5 and U6) at 0 and 24 h. No statistically significant difference (p<0.05) was found between Groups U1 and U5, U1 and U6, U2 and U3, U2 and U4, U2 and U5, U2 and U6, U3 and U4, U3 and U5, U3 and U6, U4 and U5, U4 and U6, and U5 and U6 at 0 and 24 h. CONCLUSIONS: The TP Orthodontics elastics promoted less cell lysis compared to the Uniden elastics regardless of their color.